Partial Purine Nucleoside Phosphorylase Deficiency Helps Determine Minimal Activity Required for Immune and Neurological Development - Grunebaum, Eyal; Campbell, Nicholas; Leon-Ponte, Matilde; Xu, Xiaobai; Chapdelaine, Hugo (Frontiers in Immunology, 2020)
Introduction: Complete or near complete absence of the purine nucleoside phosphorylase (PNP) enzyme cause a profound T cell immunodeficiency and neurological abnormalities that are often lethal in infancy and early childhood. We hypothesized that patients with partial PNP deficiency, characterized by a late and mild phenotype due to residual PNP enzyme, would provide important information about the minimal PNP activity sufficient for normal development. Methods: Three siblings with a homozygous PNP gene mutation (c.769C>G, p.His257Asp) resulting in partial PNP deficiency were investigated. PNP activity was semi-quantitively assayed by the conversion of [14C]inosine in hemolysates, mononuclear cells and lymphoblastoid B cells. PNP protein expression was determined by Western Blotting in lymphoblastoid B cells. DNA repair was quantified by measuring viability of lymphoblastoid B cells following ionizing irradiation. Results: A 21-year-old female was referred for recurrent sino-pulmonary infections while her older male siblings aged 25- and 28- years did not suffer from significant infections. Two of the siblings had moderately reduced numbers of T, B and NK cells while the other had near normal lymphocyte subset numbers. T cell proliferations were normal in the 2 siblings tested. Hypogammaglobulinemia was noted in 2 siblings including 1 that required immunoglobulin replacement. All siblings had typical (normal) neurological development. PNP activity in various cells from 2 patients were 8-11% of normal. All siblings had normal blood uric acid and increased PNP substrates in the urine. PNP protein expression in cells from the 2 patients examined was similar to that observed in cells from healthy controls. The survival of lymphoblastoid B cells from 2 partial PNP-deficient patients after irradiation was similar to that of PNP-proficient cells and markedly higher than the survival of cells from a patient with absent PNP activity or a patient with ataxia telangiectasia. Conclusions: Patients with partial PNP deficiency can present in the third decade of life with mild-moderate immune abnormalities and typical development. Near normal immunity might be achieved with relatively low PNP activity.